2014
DOI: 10.1002/bjs.9354
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of use of serum C-reactive protein levels to predict anastomotic leak after colorectal surgery

Abstract: CRP is a useful negative predictive test for the development of anastomotic leakage following colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
240
4
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 315 publications
(260 citation statements)
references
References 45 publications
9
240
4
7
Order By: Relevance
“…Our results achieved in young and otherwise healthy endometriosis patients therefore seem comparable with previous studies performed in patients operated for colorectal cancer [25] .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results achieved in young and otherwise healthy endometriosis patients therefore seem comparable with previous studies performed in patients operated for colorectal cancer [25] .…”
Section: Discussionsupporting
confidence: 81%
“…C-reactive protein (CRP) has been shown to be an early indicator of postoperative septic and surgical complications in abdominal and rectal surgery [21][22][23][24] and serial postoperative tests might aid detection of these major complications [25] . The aim of the present study was therefore to evaluate the diagnostic value of daily monitoring of biochemical inflammatory markers (CRP and white blood cell (WBC) count) in the diagnosis of anastomotic leakage or ureteral injury after laparoscopic bowel resection for deep infiltrating endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Some meta-analyses show that the CRP concentration on POD3-5 is a useful negative predictive test rather than a good positive predictor [20,21]. We confirmed this observation in our cohort study.…”
Section: Discussionsupporting
confidence: 81%
“…Serum CRP levels are influenced by infectious complications such as pneumonia, urinary tract infections, and wound infections [17] . Moreover, a 398 systematic review and meta-analysis reported that the positive/negative predictive values of CRP for AL were 21-23 and 97%, respectively, and concluded that CRP is a useful negative predictor of AL [18] . Based on previous reports, the CRP level may be useful for predicting AL, but it cannot be considered a definite predictor.…”
Section: Discussionmentioning
confidence: 99%